Pengaruh Marketing Mix 4p Terhadap Peningkatan Penjualan Pada UMKM di Labuhanbatu Selatan - Nurhabibah Ritonga (Jurnal Economic Resource, 2026)
This study examines the influence of the 4P marketing mix, consisting of product, price, promotion, and place, on the sales increase of Bakso Barokah Blok Songo in Labuhanbatu Selatan. The background of this research lies in the increasingly competitive culinary business environment, which demands effective marketing strategies to maintain business continuity. Using a quantitative approach with descriptive and associative methods, the study collected data from 80 respondents through questionnaires, observations, and interviews. Validity and reliability tests confirmed that all research instruments were valid and reliable, while classical assumption tests indicated that the regression model met the requirements of normality, no multicollinearity, and no heteroscedasticity. Multiple regression analysis revealed that price and place have a significant effect on sales increase, while product and promotion do not show significant effects. The F-test further demonstrated that the four marketing mix variables simultaneously influence sales increase. Meanwhile, the coefficient of determination indicated that 73.2% of the variation in sales increase can be explained by the marketing mix variables. These findings highlight the importance of setting appropriate pricing and optimizing distribution strategies to enhance sales performance in culinary SMEs. This study contributes to marketing literature in the context of local businesses and provides practical insights for improving the competitiveness of Bakso Barokah Blok Songo.